Effect of Admixture on Physical and Mechanical Properties of Recycled Brick Aggregate Concrete - Islam, Md Jahidul; Shahjalal, Md; Hasan, Md Mehedi; Chowdhury, Zarin Tasnim (MIST International Journal of Science and Technology, 2021)
With the increasing population of the world, the rate of development of infrastructure is increasing day by day; which has placed a massive demand for natural aggregates. Besides, huge amount of demolished construction wastes are generated all over the world which creates pressure on the environment as well as landfills. Therefore, it is necessary to find a sustainable solution to adopt these C&D wastes as an alternative to natural aggregates for construction purposes. Therefore, the objective of the present study is to explore the influence of superplasticizers while adopting recycled brick aggregate (RBA) in the sustainable concrete application as a coarse aggregate. Six different mixes are considered with 100% replacement of recycled brick aggregate and three diverse water-cement (w/c) ratios, such as 0.40, 0.45, and 0.50. To improve the workability and mechanical characteristics of concrete a superplasticizer is used as an admixture. Fresh properties of concrete, compressive strength at normal and high temperatures, flexural strength and splitting tensile strength are presented. The results indicate that addion of superplasticizer improves slump values and reduces air voids of concrete. Although strengths of RBA concrete are lesser than the virgin brick aggregate concrete, they are still satisfactory in the application for structural concrete and can be also significantly improved by incorporating admixture. Finally, this research will help to recycle the brick aggregate instead of dumping it as waste in a landfill. MIJST, Vol. 9(1), June 2020: 37-44